A Comparative Analysis Between RIPASA and Alvarado Scoring Systems for the Diagnosis of Acute Appendicitis- A Nepalese Perspective - Baral, Suman; Thapa, Neeraj; Chhetri, Raj Kumar; Sharma, Rupesh (Journal of Lumbini Medical College, 2018)
Introduction: Various diagnostic criteria have been described for acute appendicitis. For decades the most commonly used one has been Alvarado score. RIPASA scoring system has also been developed for Asian population which has shown highest sensitivity and diagnostic accuracy. This study aimed to compare these two diagnostic criteria in Nepalese population attending a tertiary center.Methods: Patients with clinically suspected acute appendicitis were classified according to both Alvarado and RIPASA scoring systems before undergoing surgery. Histopathological examination was taken as the gold standard for diagnosis. Statistical analysis was done using McNemar's test as applicable.Results: Ninety nine (90 %) patients had histologically confirmed appendicitis. With the cut-off value greater than 7.5 for RIPASA score; sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy and negative appendectomy rates were 94.5%, 27.27 %, 92.16 %, 37.5 %, 88.18% and 7.84% respectively. With the cut-off value greater than 7 for Alvarado score, sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy and negative appendectomy rates were 71.72%, 72.73 %, 95.95 %, 22.22%, 71.82 %, and 4.05 % respectively. 94.5% of patients were correctly stratified by RIPASA under higher probability group while only 71.8 % were classified by Alvarado (p value= 0.0001).Conclusion: RIPASA scoring system showed high sensitivity and diagnostic accuracy in comparison to Alvarado scoring system. So, this method can be applied in Nepalese setting for the diagnosis of acute appendicitis.DOI: https://doi.org/10.22502/jlmc.v6i2.264